Update of the Atlas systems conceptual framework - Dyshlyk, O.; Chabaniuk, V. (Land Management, Cadastre and Land Monitoring, 2024)
Over the past ten years, the Conceptual Framework with the necessary changes has been repeatedly used in projects to create various Electronic Atlases, including the Electronic version of the National Atlas of Ukraine (ElNAU), Atlas Information Systems, and even GeoInformation Systems. At the same time, both practical tools and theoretical methods changed and evoluted. Both practical and theoretical activities continue and are very actual today. However, there was no separate publication on the current state of the Conceptual Framework of subject X, where X would assume the meaning of modern systems. In order to improve, expand and simplify its practical and theoretical usages, it is necessary to fix the main updates of the entire structure: both the Conceptual Framework itself, and the subject X, to which it is appropriate to apply it. Therefore, instead of the subject X = ElNAU, subjects-systems from the set AtS = Atlas Systems ’ X are considered, and the Conceptual Framework itself is presented as a system method corresponding to the system approach, with an emphasis on design, although the Conceptual Framework can also be used for the study of systems, i.e. be a research method. Over ten years, the Conceptual Framework of subject X has become a rather extensive phenomenon, which forced us to stop only at the main (at least for us) updates. Keywords: Atlas Systems (AtS), Conceptual Framework of AtS, Atlas infrastructure, AtS in the broder sense (AtSb).